Population Characteristic and Genetic Relationship on 25 Bengkulu Heirloom Rice Based on Morpgological Traits - Rustikawati, Rustikawati; Simarmata, Marulak; Pujiwati, Hesti; Herison, Catur (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2019)
Bengkulu Province has many local rice germplasms that have adapted to specific areas. The germplasm has certain character advantages so that it is maintained by farmers. The characteristics of each germplasm need to be identified in order to improve the properties of the existing germplasm. This study aimed to determine the performance, to estimate the value of genetic parameters, and to determine the genetic relationship of local rice genotypes collected from four districts in Bengkulu Province. The results showed that the ‘Kuning Sulaowangi’ genotype was the earliest in maturity had the highest number of tillers amongst genotypes. Genotypes which have significantly the highest average component yields were ‘Kunig Air Dingin’ and ‘Impera’. Traits that have a high heritability estimated value were weight of 100 grains (91.046%) and grain weight per panicle (80.252%). The weight of 100 grains also has the highest genetic variability value. Thus increasing local rice production is possible. Based on the results of the analysis with the similarity coefficient of 55%, the local rice genotypes could be grouped into two groups. Group I consisted of 9 genotypes namely ‘Kuning Pendek’, ‘Humbur’, ‘Cantik’, ‘Pandak Kelabu’, ‘Cisadane Putih’, ‘Kuning Sulaowangi’, ‘China Abang’, ‘China Putih’ and ‘Impera’. Other genotypes were in Group II. Trait improvement can be done through hybridization between individuals of different groups. To develope early in maturity and high-yielding varieties can be done through hybridization of the ‘Kunig Sulaowangi’ and ‘Kunig Air Dingin’